PENGARUH INISIASI MENYUSU DINI TERHADAP PENCAPAIAN INVOLUSI ITERUS PADA IBU POST PARTUM - Rakhamayanti, Ima; Eka P., Veryudha (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Early initiation is one of the factors that affeet uterine involution occurs during breastfeeding because stimulation and release of hormones such as oxytocin which stimulates contraction of muscle function in addition to smooth-muscle breakst, also causes contraction and retraction of uterine muscles. This research aimed to determine the effect if early initiation to acceleration in mother postpartum uterine involution in Katemas Village independent practice Midwife (IPM) Kudu Sub District Jombang District. Design research in an observation correlation with the analytic approach prospective cohort. The population were all postpartum mothers in the Katemas Village IPM Kudu Sub District Jombang District, using purposive sampling technique samples obtained 13 samples. The result showed that the application of early breastfeeding initiation most successful is as many as 76.9% and maternal postpartum uterine involution was normal as many as 61.5%. Analysis of the data used is Wilcoxon test where a = 0.046 <0.05 then H0is rejected, so there is the influence of the acceleration of early initiation of breastfeeding in mothers postpartum uterine involution in in Katemas Village Independent Practice Midwife (IPM) Kudu Sub District Jombang District. Early initiation of breastfeeding can accelerate uterine involution due to sucking stimulates the posterior pituitary to release oxytocin which is useful for the contraction of smooth muscles of the uterus so that the procces uterine muscle return to its original state can occur earlier.